The Effect of Macroeconomic Variables on Company Stock Prices with Inflation as a Moderating Variable on the Indonesian Mining Industry - Fajarini, Yuliatussolihah; Ari Darmawan (FIA UB, 2024)
This study uses signalling theory and purchasing power parity theory to determine the effect of world oil prices, interest rates, and exchange rates on company stock prices, with inflation as a moderating variable. As explanatory research with a quantitative approach, this study selects a sample of 29 Indonesian mining companies through a purposive sampling technique. Data analysis used E-Views 12 software, which included descriptive analysis, classic assumption test, panel data regression test, moderation regression test, hypothesis test (t-test), and determination test. The results of this study show that the variables of World Oil Prices and Interest Rates partially have a positive and significant effect on Stock Prices. Exchange rates have a negative and significant effect on stock prices, and inflation has no moderating effect on the world oil price, interest rate, and exchange rate on stock prices.